Corporate Governance Practices and Capital Structure: Evidence from Malaysian Capital Market - Nazaria, Md. Aris; Suzila, Mohamed Yusof; Kerk, Yee Xuan; Nurul Syuhada, Zaidi; Ahmad Syubaili, Mohamed (Human Resource Management Academic Research Society, 2021)
Corporate Governance has become the most inevitable issues around the world as the emergence of prominent corporate scandals, for example, Enron and WorldCom. It was also known as an important key of leading good financing decision in a company. The motivation behind this project sought to investigate the influences of the Corporate Governance practices on capital structure decision among Top 100 companies for overall Corporate Governance and performance in Malaysian Capital Market over the period 2012 to 2016. All data was gathered from annual report of Malaysian listed firms in Bursa Malaysia Stock Exchange, excluding the financial companies due to their special rules and regulation in their Corporate Governance system. This study has been employed descriptive analysis, correlation analysis and fixed effects regression model to find out the research objectives. Results from the research indicate that board gender, independence audit committee, and profitability were statistically negative to leverage. Further, the research also found that large firm size with high managerial ownership will pursue high debt policy. Nonetheless, debt- to-equity ratio has no zero relationship with board size and board independence. These findings will be useful to the policymaker to formulate Corporate Governance mechanisms as well asinvestorsfor assessing the listed companiesin Malaysia before making investment decision.